Intimidating competitors: Endogenous vertical integration and downstream investment in successive oligopoly - Stefan Bühler; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2005)
We examine the interplay of endogenous vertical integration and costreducing downstream investment in successive oligopoly. We start from a linear Cournot model to motivate our more general reducedform framework. For this general framework, we establish the following main results: First, vertical integration increases own investment and decreases competitor investment (intimidation effect). Second, asymmetric equilibria typically involve integrated firms that invest more into efficiency than their separated counterparts. Our findings suggest that asymmetric vertical integration is a potential explanation for the initial difference between leader and laggard in investment games.
Keywords: L13; L20; L22; 330; vertically related oligopolies; investment; vertical integration; cost reduction; Vertikale Konzentration; Investitionsentscheidung; Oligopol; Nash-Gleichgewicht; Marktstruktur